Soybean Drought Tolerance and Escape: Field Trial Assessment of Yield, Maturity Groups and Smooth-Wrinkled Seed Coats in Kazakhstan - Raushan Yerzhebayeva; Svetlana Didorenko; Sholpan Bastaubayeva; Aigul Amangeldiyeva; Bekzhan Maikotov; Rinat Kassenov; Yuri Shavrukov (Agriculture)
Soybean is a major legume and oilseed crop with enormous economic importance, but its production is highly dependent on optimal rainfall or ample irrigation. In Kazakhstan, soybean production is highly vulnerable to drought and irrigation shortages. The aim of this study was to assess the level of drought escape and tolerance of soybean genotypes in different maturity groups, grown in well-watered conditions or without irrigation. Field trials were conducted in the very dry conditions of Kazakhstan with the hydrothermal coefficient 0.46–0.67. Nineteen soybean cultivars from five maturity groups were tested over four seasons under two conditions, with and without irrigation. The main indicators of drought tolerance were seed yield, seed weight per plant, percentage of seeds with smooth coats compared to wrinkled and shriveled ones, and 1000 seed weight. Under drought, seed yield of the studied genotypes decreased by 45.5–69.5% compared to well-watered controls. The most optimal genotypes for cultivation without irrigation were soybean cultivars from medium maturity group MG I (Vilana, Cheremosh, Xin-D11-252, and Desna) with a vegetation period of 115–128 days when avoiding drought during flowering, and the average yield for the group (1.7 t/ha) was slightly below that of those in drought-tolerant genotypes from medium–late/late maturity groups MG II–III (1.9–2.0 t/ha). Based on yield under drought, the best cultivars were identified as follows: Ivushka (1.2 t/ha) for MG 00 group; Ustya (1.3 t/ha) for MG 0; Vilana (1.8 t/ha) for MG I; Zen (2.3 t/ha) for MG II; and Sponsor (2.5 t/ha) for MG III. The identified genotypes can be used in breeding programs to reduce drought effects on soybean crops.